Wasted septal work in left ventricular dyssynchrony: a novel principle to predict response to cardiac resynchronization therapy. (25th February 2016) - Vecera, J.; Penicka, M.; Eriksen, M.; Russell, K.; Bartunek, J.; Vanderheyden, M.; Smiseth, O.A.
Abstract: Aims: Cardiac resynchronization therapy (CRT) in heart failure is limited by many non-responders. This study explores whether degree of wasted left ventricular (LV) work identifies CRT responders. Methods and results: Twenty-one patients who received CRT according to guidelines were studied before and after 8 ± 3 months. By definition, segments that shorten in systole perform positive work, whereas segments that lengthen do negative work. Work was calculated from non-invasive LV pressure and strain by speckle tracking echocardiography. For each myocardial segment and for the entire LV, wasted work was calculated as negative work in percentage of positive work. LV wall motion score index (WMSI) was assessed by echocardiography. Response to CRT was defined as ≥15% reduction in end-systolic volume (ESV). Responder rate to CRT was 71%. In responders, wasted work for septum was 117 ± 102%, indicating more negative than positive work, and decreased to 14 ± 12% with CRT ( P < 0.01). In the LV free wall, wasted work was 19 ± 16% and showed no significant change. Global LV wasted work decreased from 39 ± 21 to 17 ± 7% with CRT ( P < 0.01). In non-responders, there were no significant changes. In multiple linear regression analysis, septal wasted work and WMSI were the only significant predictors of ESV reduction ( β = 0.14, P = 0.01; β = 1.25, P = 0.03). Septal wasted work together with WMSI showed an area under the curve of 0.86 (95% confidence interval 0.71–1.0) for CRT response prediction. Conclusion: Wasted work in the septum together with WMSI was a strong predictor of response to CRT. This novel principle should be studied in future larger studies.